Liquefaction and Reliquefaction Characteristics of Aeolian Sand Foundation Reinforced by Precast Cement Piles Based on Shaking Table Test. (7th November 2022) - Zhu, Zhaorong; Zhou, Yuan; Han, Kan; Wu, Honggang; Zhao, Shouquan
Abstract : With the continuous development of traffic construction, road engineering inevitably crosses the aeolian sand river valley area. Compared with general sandy soil and silty soil, cohesionless aeolian sand foundation has similar properties with fluid and higher liquefaction potential. Precast cement pile can greatly improve the vertical bearing capacity of foundation, but this paper finds that it also has antiliquefaction effect when it is used to reinforce aeolian sand foundation. In addition, there may be more than one liquefaction of aeolian sand foundation in areas with frequent earthquakes. Therefore, this paper explores the liquefaction and reliquefaction characteristics of aeolian sand foundation reinforced by precast cement piles through shaking table test. The test results show that under the excitation of 0.4 g EL Centro wave: (1) the increase of pore pressure in aeolian sand foundation will have multiple instantaneous peaks, which will promote the surface to float or sink. The phenomenon will be weakened by multiple earthquakes or pile reinforcement. (2) The prefabricated cement pile can improve the liquefaction and reliquefaction resistance of aeolian sand foundation. The effect is the best in the shallow layer of the foundation, which is increased by more than 30%, and the deeper the buried depth, the lower the effect. (3) The antiliquefaction ability of foundation will be improved after strong earthquake, but the dynamic response will be significantly increased in the next earthquake. (4) When the aeolian sand foundation reinforced by precast cement piles is reliquefied, the main frequency of the foundation will migrate to low frequency. The liquefied layer will inhibit the low frequency (2 ~ 15 Hz) energy transfer and promote the high frequency (25~30 Hz) energy transfer. The results provide reference for antiliquefaction design of aeolian sand foundation and improve the application of precast cement pile in liquefied foundation.